Molecular Layering Synthesis and Investigation of Nanostructured Oxide Layers in High Aspect Ratio Substrates - A. P. Baraban; V. A. Dmitriev; A. V. Drozd; V. A. Moshnikov (Известия высших учебных заведений России: Радиоэлектроника, 2024)
Introduction. Solid-state electron multipliers (EMs) in matrix design, referred to as microchannel plates (MCPs), are an integral part of modern electronics. Recent progress in the field of molecular layering (ML) technology has offered an opportunity to tailor and improve the characteristics of solid-stated EMs by depositing thin layers inside the channels of these structures.Aim. To study the possibility of depositing thin layers inside the surface of solid-state EM channels by ML in order to increase the secondary electron emission coefficient (SEEC) of such structures, thereby improving their performance characteristics.Materials and methods. The ML method was used to deposit nanometer films of magnesium and aluminum oxides inside solid-state EM channels. The composition and structure of the layers were studied using scanning electron microscopy, X-ray photoelectron spectroscopy, secondary electron emission analysis, and atomic force microscopy.Results. Thin aluminum oxide and magnesium oxide films were synthesized inside the micron channels of solidstate EMs. The layers exhibited high uniformity along the entire length of the channels. The layer thickness varied in the range from 2 to 30 nm. Layers with improved emission and protective characteristics were obtained. Comparative tests of MCP samples containing the synthesized films were carried out.Conclusion. Good prospects for the application of emissive layers inside solid-state EM channels were shown. Structures with a high aspect ratio are promising objects for ML application. The creation of nanocomposite structures based on MCPs opens up the fundamental possibility of improving the current technology of producing electrooptic materials and devices. The MCP structures containing aluminum oxide layers obtained by ML technology were experimentally tested to detect beam collisions (FBBC) for work in detectors at the NICA accelerator complex. Following deposition of a 3.0 nm-thick Al2O3 film in the channels of the tested MCP samples, the signal amplitude increased by 1.5 times. The deposition of layers with a film thickness of 10 nm resulted in a 2.5-fold increase in the amplitude.